Avaliação dos pacientes submetidos à prostatectomia radical e seu desfecho quanto à disfunção erétil em Hospital Universitário - Perassol, Vinícius Pereira (2024)
Introduction: Prostate cancer, highly prevalent, is often treated with Radical Prostatectomy (RP). A common complication associated with this procedure is erectile dysfunction (ED), influenced by factors such as age, comorbidities, and tumor characteristics. Objective: To assess the prevalence and factors associated with ED in patients undergoing RP at a school hospital, considering age, comorbidities (hypertension and diabetes), use of adjuvant radiotherapy (RT), tumor staging, and preoperative PSA levels. Casuistic and Methods: This retrospective study included 180 patients who underwent RP between 2017 and 2019. Data on age, comorbidities, cellular differentiation grade (ISUP), and PSA were collected from medical records. Statistical analysis included chi-square tests, likelihood ratios, and Pearson's correlation to evaluate the association between ED and clinical factors. Results: The average age of patients was 64 years. It was observed that 43.1% of patients without ED and 29.5% with ED underwent RT. Higher ISUP scores were associated with a greater prevalence of ED, suggesting a relationship between tumor aggressiveness and this complication. PSA levels and the presence of hypertension and diabetes showed no significant correlation with ED. Conclusions: Tumor aggressiveness, measured by the ISUP score, is associated with a higher occurrence of ED post-RP. Adjuvant radiotherapy showed a trend toward reducing the incidence of ED but without statistical significance. Personalized management strategies in prostate cancer treatment may help minimize ED's impact on the patient´s quality of life.